2014
DOI: 10.5539/ijef.v6n7p242
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relationship between Corporate Governance Ratings and Company Value: Empirical Evidence for S&P 100 Companies

Abstract: The goal of the current study is to examine the relationship between corporate governance ratings and company value, for all the companies included in the S&P 100 Index, with the exception of companies involved in the financial sector, using data for 2013. The value of the company is quantified using the Tobin's Q ratio and the Enterprise Value, adjusted according to each activity sector. The corporate governance practices are reflected using the ISS Governance QuickScore 2.0 overall rating, provided by the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Their findings yield consistent weak results about a systematic relation between the indexes and performance. More recently, Gherghina et al (2014) reported a lack of a statistically significant relationship between ISS CGR and company value for a limited US large firms sample.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Their findings yield consistent weak results about a systematic relation between the indexes and performance. More recently, Gherghina et al (2014) reported a lack of a statistically significant relationship between ISS CGR and company value for a limited US large firms sample.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…This is, to our knowledge, the second study using this specific rating. In a prior study with a limited sample of US firms, Gherghina et al (2014) reported the lack of a statistically significant relationship with the companies’ value. While our research shares some similarities with Gherghina et al (2014), unlike them, we investigate a large sample of firms from 16 European countries following a cross-regional approach.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…From other side, some prior studies reported opposed results. ISS Governance QuickScore 2.0 overall rating is used by Gherghina et al (2014) that are provided by the Institutional Shareholder Services Inc. (ISS) to reflect the corporate governance practices for each and every company that is a part of S&P 100 Index. Therefore, only the companies involved in the financial sector were left as an exception.…”
Section: Corporate Governance Index and Firm Valuementioning
confidence: 99%